Role of fiberoptic endoscopic evaluation of swallowing (FEES) in children with suspected dysphagia - Débora Bressan Pazinatto; Maria Angela Bellomo Brandão; Flávia Lima Peixoto Costa; Myrian Maria Andreotti Favaro; Rebecca Maunsell (Elsevier, 2024)
Objective: To assess FEES findings in defining oral feeding safety in children with suspected dysphagia, comparing them with clinical feeding evaluation results. Methods: This study comprised a case series involving children with suspected dysphagia, referred for evaluation by otolaryngologists and speech-language pathologists (SLPs) at a Brazilian quaternary public university hospital. These children underwent both clinical evaluations and fiberoptic endoscopic evaluation of swallowing (FEES), with a comprehensive collection of demographic and clinical data. Subsequently, the authors performed a comparative analysis of findings from both assessments. Results: Most patients successfully completed the FEES procedure (93.7%), resulting in a final number of 60 cases included in the study. The prevalence of dysphagia was confirmed in a significant 88% of these cases. Suspected aspiration on clinical SLP evaluation was present in 34 patients. Of these, FEES confirmed aspiration or penetration in 28 patients. Among the 35 patients with aspiration or penetration on FEES, 7 (20%) had no suspicion on SLP clinical assessment. All seven patients in whom clinical SLP evaluation failed to predict penetration/aspiration had neurological disorders. The median age of the children was 2.8 years, and 49 (81.6%) had neurological disorders, while 35 (58.3%) had chronic pulmonary disease. The most prevalent complaints were choking (41.6%) and sialorrhea (23.3%). Conclusion: FEES can diagnose structural anomalies of the upper aerodigestive tract and significantly contribute to the detection of aspiration and penetration in this group of patients with suspected dysphagia, identifying moderate and severe dysphagia even in cases where clinical assessment had no suspicion.